History of Innovative Entrepreneurs in Japan - Kikkawa, Takeo (Springer Nature, 2023)
This is the first Open Access book introducing more than 20 of Japan's leading innovative entrepreneurs from the 17th century to the present. The author outlines the innovative business models created by entrepreneurs including SoftBank's Masayoshi Son, Fast Retailing (Uniqlo)'s Yanai Tadashi, Honda's Soichiro Honda, Sony's Akio Morita, Panasonic's Konosuke Matsushita, and Toyota's Kiichiro Toyoda, as well as their predecessors including Takatoshi Mitsui of Mitsui Zaibatsu, Shibusawa Eiichi of Daiichi Bank. While introducing the innovators, the author also raises three broader questions: 1. Why did Japan industrialize earlier than any other country outside Europe and the United States? 2. Why was Japan able to realize unsurpassed economic growth between the 1910s and the 1980s? 3. Why has Japan's economy stagnated for more than 30 years since the 1990s? Drawing upon analytical concepts including Schumpeter's breakthrough innovation, Kirzner's incremental innovation, and Christensen's disruptive innovation, the author contends that Japan's successes were based on unique and systematic breakthrough innovation and an accumulation of incremental innovation, while it later fell victim to a combination of breakthrough innovation from advanced countries and disruptive innovation by developing nations.